(untitled) (Proceedings of the International Conference on Future of Education, 2021)
One of the teaching models which stimulates and motivates students’ studying activities is the flipped class, which “turns over” the traditional order of the material (a lecture - homework) vice versa. The purpose of this work is to present the effectiveness of the usage of the flipped class model when teaching international students’ theoretical disciplines in Russian at the philological faculty at Pushkin State Russian Language Institute. The traditional way of giving the material of theoretical disciplines to the international students didn’t show the high results: the students couldn’t master the material in full, didn’t understand texts of the lectures due to an insufficiently formed lexical stock and couldn’t do practical tasks and tests. The students met significant difficulties during the performance of the certification work. It became clear that the special preparative work must be done with the students before they begin to listen to lectures. So, the teaching and academic staff of the department (Department of Methodology of Teaching Russian as a Foreign Language) at the philological faculty decided to change the traditional way of giving theoretical lecture material in Russian for the international students into the flipped class teaching model. In 2019-2020 academic year the international students got the new formatted material under study within the theoretical discipline “Aspect study of the Russian Language in an international audience”. LMS Canvas was used as an educational platform, where the students got different tasks with video lectures, articles, questions, practical exercises. At the end of the term the students completed the certification work. And the high points which the students got for the work indicated the correctness of the chosen teaching model.